Increased circulating cell-derived microparticle levels in deep infiltrating endometriosis patients with larger implants. Issue 3 (September 2019) - Munrós, Jordina; Tàssies, Dolors; Reverter, Joan Carles; Carmona, Francisco; Martínez-Zamora, María Ángeles
Objective: Circulating cell-derived microparticles have been reported to be elevated in inflammatory and procoagulant conditions including deep infiltrating endometriosis. The objective of this pilot study was to investigate whether higher circulating cell-derived microparticle levels may be associated with specific clinical features and the extension or severity of deep infiltrating endometriosis. Methods: This is an observational analytical cross-sectional study, including three groups of patients undergoing gynecological surgery. The DIE group included 75 patients with deep infiltrating endometriosis, the control group (C group) consisted of 39 patients without endometriosis, and a positive control group was composed of 31 patients with ovarian endometriomas but not deep infiltrating endometriosis (OE group). Venous blood samples for circulating cell-derived microparticle determinations in plasma were obtained before surgery. The following variables were assessed: severe dysmenorrhea, dyspareunia, non-cyclic chronic pelvic pain, dyschezia, dysuria, hematuria, rectal bleeding, sterility, presence of ovarian endometrioma, adenomyosis, and adhesions, rASRM (revised American Society for Reproductive Medicine) stage, Enzian classification, number of sites affected, and the cumulative size of deep infiltrating endometrial implants. Results: Circulating cell-derived microparticle levels were statistically higher in the DIE group compared with the C group ( p -value = 0.001). None of the variables analyzed showed higher levels of circulating cell-derived microparticles in the DIE group, except for a significant positive correlation between the cumulative size of deep infiltrating endometrial lesions and circulating cell-derived microparticle levels ( r = 0.264, p = 0.022). Conclusion: Patients having deep infiltrating endometriosis with a larger cumulative size of endometriotic implants showed higher circulating cell-derived microparticle levels suggesting an increased inflammatory and/or hypercoagulable systemic status in this more severe form of the disease. Further research is needed to assess our findings and to explore the role of circulating cell-derived microparticles in the pathophysiology of deep infiltrating endometriosis.